Shift work as a predictor of hearing protection devices use among manufacturing workers in Selangor, Malaysia - Sam, Wei Yeng; Abdul Rahman, Anita; Kadir @ Shahar, Hayati; Abdullah, Haslinda; Lim, Chee Siang (Community Health Society Malaysia, 2016)
Background: World Health Organization estimated hearing loss to reach top ten causes of burden of disease by 2030. Employers still prefer to choose hearing protection devices (HPDs) for prevention. Predictors for HPDs use were therefore crucial but only a few look into the effect of shift work. This study aimed to determine whether shift work is a predictor for HPDs use. Materials and Methods: A cross-sectional study was conducted among 180 randomly selected participants from nine manufacturing companies in small medium enterprise who fulfilled inclusive criteria and information were gathered by self-administered questionnaires. Result: Mean HPDs use was 38.13 ±31.84% and mean HPDs use during high noise exposure was 39.19 ±30.99%. Shift workers had statistically significant higher HPDs use (50.34 ±31.32%) than non-shift workers (33.93 ±31.04%), t (178) =3.086, p=.002. There was significant difference between HPDs use and sleep problem. There were weak but negative association between shift work and HPDs use during high noise exposure [χ (3) =12.257, p=.007]. Association between shift work and sleep problem was significant [χ (2) =7.21, p=.027] but weak, it was negatively associated. Conclusion: Continuous rotation of shift work might lead to circadian rhythm alteration and affect sleep quality. Noise might worsen the situation hence further investigation is needed to examine if improper use of HPDs was related with sleep problems. Shift workers reported higher HPDs use and it might be due to less need of removing and putting on HPDs. Shift work may be a predictor for HPDs use among manufacturing workers.